Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

A voice from the South - Cooper, Anna Julia (University of North Carolina at Chapel Hill Library, 2017)
The first book by Anna J. Cooper, A Voice From the South, presents strong ideals supporting racial and gender equality as well as economic progress. It’s a forward-thinking narrative that highlights many disparities hindering the African American community. Anna J. Cooper was an accomplished educator who used her influence to encourage and elevate African Americans. With A Voice From the South, she delivers a poignant analysis of the country’s affairs as they relate to Black people, specifically Black women. She stresses the importance of education, which she sees as a great equalizer. Cooper considers it a necessary investment in not only the individual but the community. She also criticizes the depictions of African Americans in literature by some of the day’s most popular authors. She calls for more realistic portrayals that are both honest yet positive. Cooper provides an unflinching critique of mainstream America as it relates to the Black population. A Voice From the South broaches pivotal topics such as women’s rights, segregation and the need for higher education. With an eye-catching new cover, and professionally typeset manuscript, this edition of A Voice From the South is both modern and readable.
Keywords: 1800-1899; afro-féminisme; amériques; approches et analyses; capitalisme; droits des femmes*; féminismes noirs; histoire et politique; militance; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; éducation; états-unis

Un autre regard : trucs en vrac pour voir les choses autrement - Emma (Massot éditions, 2017)
Avec, une dizaine d'histoires très variées autour du Féminisme, de la politique ou de la sexualité, cette jeune blogueuse casse les clichés sur bon nombre de sujets. A l'opposé des stéréotypes, elle dévoile notamment son expérience de jeune maman au travers d'une série d'anecdotes tout sauf édulcorées. En revisitant avec beaucoup de justesse et d'engagement des sujets tels que le sacro-saint instinct maternel, le baby blues, l'histoire du clitoris ou encore les violences policières, elle parvient à remettre en question des vérités qui pourraient paraître établies. Cette bande dessinée est aussi drôle que touchante et instructive
Keywords: approches et analyses; bande-dessinée; charge mentale; corps; europe; france; maternité; militance; patriarcat; projet charge mentale; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; violences

THE COLOURED WOMEN’S CLUB OF MONTREAL, 1902-1940: African-Canadian women confronting anti-black racism - Este, David; Sato, Christa; McKenna, Darcy (Canadian Social Work Review, 2017)
À ce jour, il existe très peu d’écrits sur la contribution des personnes d’ascendance africaine à l’histoire de l’assistance sociale canadienne. À partir de sources secondaires et archivistiques, nous analysons la contribution du Club des femmes de couleur de Montréal (CFCM) au bien-être de la communauté noire de Montréal entre 1902 et 1940 du point de vue du racisme contre les Noir.e.s et du féminisme afro-canadien. Le CFCM a joué un rôle prépondérant dans ce bien-être en étant l’un des grands soutiens auprès des membres aux prises avec d’importantes difficultés dans une société où le racisme était omniprésent et où les perspectives d’avenir pour les hommes et les femmes étaient fortement limitées. Le club a organisé plusieurs activités qui ont permis aux membres de la communauté de survivre dans un milieu hostile aux personnes d’ascendance africaine. Il a ainsi été d’un grand secours et a favorisé un sentiment de communauté chez les Noir.e.s de Montréal. Nous avançons que, grâce aux efforts de ce club durant cette période, les Afro-Canadiennes sont d’abord devenues des actrices clés de la communauté et ensuite les premières intervenantes sociales. Il est impératif que les travailleurs sociaux reconnaissent la contribution des femmes engagées dans le CFCM afin de faire contrepoids aux récits historiques de notre profession qui proviennent surtout d’une culture hégémonique blanche.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; amériques; approches et analyses; canada; cours; fem3100; femmes* afro-descendantes; histoire et politique; militance; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Making space for Indigenous feminism - Green, Joyce A. (Fernwood Publishing, 2017)
The 2007 first edition of this book proposed that Indigenous feminism was a valid and indeed essential theoretical and activist position, and introduced a roster of important Indigenous feminist contributors. The book has been well received nationally and internationally. It has been deployed in Indigenous Studies, Law, Political Science, and Women and Gender Studies in universities and appears on a number of doctoral comprehensive exam reading lists. The second edition, Making More Space, builds on the success of its predecessor, but is not merely a reiteration of it. Some chapters from the first edition are largely revised. A majority of the chapters are new, written for the second edition by important new scholars and activists. The second edition is more confident and less diffident about making the case for Indigenous feminism and in deploying a feminist analysis. The chapters cover issues that are relevant to some of the most important issues facing Indigenous people--violence against women, recovery of Indigenous self-determination, racism, misogyny, and decolonisation. Specifically, new chapters deal with Indigenous resurgence, feminism amongst the Sami and in Aboriginal Australia, neoliberal restructuring in Oaxaca, Canada's settler racism and sexism, and missing and murdered Indigenous women in Canada."-- Résumé de l'éditeur.
Keywords: amériques; approches et analyses; australie; canada; cours; discipline; droits des femmes*; droits des personnes autochtones; féminisme autochtone; histoire et politique; justice sociale; mexique; militance; océanie; patriarcat; pol4105; premier cycle; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones; études décoloniales; études féministes

De la marge au centre : théorie féministe - hooks, bell (Cambourakis, 2017)
Avec "De la marge au centre", son deuxième essai paru aux États-Unis en 1984, bell hooks poursuit la réflexion initiée dans "Ne suis-je pas une femme?" Étudiant les succès et les manquements des mouvements féministes qui ont traversé le xxe siècle, elle constate l'échec de la création d'un féminisme de masse qui s'adresserait à toutes. Elle s'attache ainsi, dans un style toujours accessible, à bouleverser les représentations habituelles de la pensée féministe majoritaire en plaçant au centre de sa réflexion les femmes noires et/ou des milieux populaires, insistant sur le besoin profond d'une approche révolutionnaire de ces questionnements. Cet ouvrage percutant a imposé bell hooks comme l'une des voix les plus influentes et stimulantes de la scène féministe.
Keywords: 1900-1999; EDI; afro-féminisme; amériques; approches et analyses; black feminism; classe sociale; com5170; cours; discours dominant; fem1000; femmes* noires; féminismes noirs; histoire du féminisme; incontournable; justice sociale; militance; mouvements féministes; pol4212; premier cycle; périodes historiques; racisme; régions géographiques; sex3383; sexisme; systèmes d'oppressions; thématiques; théorie féministe; états-unis

Deer Woman: an anthology - LaPensée, Elizabeth; Alvitre, Weshoyot; Stonefish, Patty; Vasquez, Allie; Naragon, Rebecca; Thunder, Jonathan; Native Realities (Firm); Arming Sisters (Organization) (Native Realities, LLC, 2017)
Based on the true stories of Indigenous women throughout the world, Deer Woman: An Anthology is an extension of the Deer Woman: A Vignette, comic book that itself is a powerful expression and weaves the stories of Deer Woman into a modern narrative of the struggles of Indigenous women in North America. This anthology features the work of more than a dozen Native women sharing stories of survival, empowerment, and healing. Edited by Elizabeth LaPensée and Weshoyot Alvitre and featuring the work of: Patty Stonefish, Allie Vasquez, Mia Casesa, Darcie Little Badger, Tara Ogaick, Kimberly Robertson, Barbara Kenmille, Maria Wolf Lopez, Tatum Bowie, Jackie Fawn, Rebecca Roanhorse, Carolyn Dunn, Nashoba Dunn-Anderson, and more, this anthology is an important addition to the current conversation about violence against women, especially Native women.-from publisher's website.
Keywords: amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; bande-dessinée; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

Le positionnement intersectionnel comme pratique de recherche: faire avec les dynamiques de pouvoir entre femmes - Marcillat, Audrey; Miramond, Estelle; Rupert, Nouri; Çıngı Kocadost, Fatma (Les cahiers du CEDREF, 2017)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; cours; discipline; intersectionnalité; inégalités; militance; premier cycle; pédagogie; périodes historiques; régions géographiques; sciences humaines; sexisme; soc3113; sociologie; systèmes d'oppressions; thématiques; états-unis

Femmes autochtones: la violence coloniale et ses avatars - Perreault, Julie (Relations, 2017)
Au Québec et au Canada, les femmes autochtones sont parmi les plus susceptibles d'être la cible de violences; une réalité qui met en lumière une histoire de colonialisme qui continue de faire des victimes.
Keywords: amériques; approches et analyses; canada; cours; discipline; femmes* autochtones; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; québec; racisme; régions géographiques; science politique; science politique et droit; sex2283; sexisme; système colonial; systèmes d'oppressions; thématiques; violences